1974
DOI: 10.1002/kin.550060204
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the acid hydrolysis of aromatic o‐carboxyamides and relative imides

Abstract: The kinetics of N-phenylphthalamic acid and of N-phenylphthalimide hydrolysis in aqueous solutions of sulfuric acid has been studied. A reaction mechanism is proposed implying that unreactive forms of the reactant appear by protonization of the amide bond at the carbonyl oxygen and by dissociation of the o-carboxyl group (N-phenylphthalamic acid). Attack of the nonprotonized amide bond by the hydroxonium ion is suggested to be the rate-limiting step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The most favorable site for protonation is commonly believed to be the carbonyl oxygen atom [18][19][20][21]. Nuclear magnetic resonance (NMR) studies have shown that virtually all amides in concentrated sulfuric acid solutions are of the O-protonated form [22,23]. Huang et al [24] and Mindrup and Schneider [25] believed that the reaction of neutral amides with electrophiles such as H + occurs on O instead of N. A typical amide, N,NDimethylformamide (DMF), interacts with H + and forms DMFH + [26] as Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most favorable site for protonation is commonly believed to be the carbonyl oxygen atom [18][19][20][21]. Nuclear magnetic resonance (NMR) studies have shown that virtually all amides in concentrated sulfuric acid solutions are of the O-protonated form [22,23]. Huang et al [24] and Mindrup and Schneider [25] believed that the reaction of neutral amides with electrophiles such as H + occurs on O instead of N. A typical amide, N,NDimethylformamide (DMF), interacts with H + and forms DMFH + [26] as Fig.…”
Section: Introductionmentioning
confidence: 99%